Holistic approach to entry order effects in the emerging markets : a study of the Asian transitional economics. - Ng, Sin Hui. (2008)
Limited to the scope of Asian emerging markets that are transiting from a command economy to a free-market system, this research seeks to determine empirically the extent to which a foreign firm that achieves the requisite fit will perform better than one that does not achieve the requisite match.